Unexpected Amanita phalloides-Induced Hematotoxicity—Results from a Retrospective Study - Miranda Visser; Willemien F. J. Hof; Astrid M. Broek; Amanda van Hoek; Joyce J. de Jong; Daan J. Touw; Bart G. J. Dekkers (Toxins, 2024)
Introduction: Amanita phalloides poisoning is a serious health problem with a mortality rate of 10–40%. Poisonings are characterized by severe liver and kidney toxicity. The effect of Amanita phalloides poisonings on hematological parameters has not been systematically evaluated thus far. Methods: Patients with suspected Amanita phalloides poisonings were retrospectively selected from the hospital database of the University Medical Center Groningen (UMCG). Medical data—including demographics; liver, kidney, and blood parameters; treatment; and outcomes—were collected. The severity of the poisoning was scored using the poison severity score. Results: Twenty-eight patients were identified who were admitted to the UMCG with suspected Amanita phalloides poisoning between 1994 and 2022. A time-dependent decrease was observed for hemoglobin and hematocrit concentrations, leukocytes, and platelets. Six out of twenty-eight patients developed acute liver failure (ALF). Patients with ALF showed a higher increase in liver enzymes, international normalized ratios, and PSS compared to patients without ALF. Conversely, hemoglobin and platelet numbers were decreased even further in these patients. Three out of six patients with ALF died and one patient received a liver transplant. Conclusion: Our study shows that Amanita phalloides poisonings may be associated with hematotoxicity in patients. The quantification of hematological parameters is of relevance in intoxicated patients, especially in those with ALF.